Studies on combinative sterilization method to seed for plant organic nutrient experiments - MO Liang-yu; WU Liang-huan; TAO Qin-nan (浙江大学学报. 农业与生命科学版)
Obtaining sterile seedlings from seeds is an important step for plant organic nutrition experiments. The plant seeds of Chinese cabbage, Pai-tsai, green gram, rice and wheat were sterilized with different combinations of three sterilizing solutions (70% ethanol, 0.1% HgCl2 and 2%NaCIO or 10%H2O2) in the experiments. The results showed that the effectiveness of combinative sterilization to plant seed was affected by plant species and seed storage time. The combinative sterilization procedure recommended was the following.①Seeds were firstly immersed in ethanol (70% V/V) for 1 min and then rinsed three times with sterile distilled water. ②Secondly immersed in sodium hypochlorite solution (2%NaCIO active constituents) for 5 min and then rinsed five times with sterile distilled water. ③Finally immersed in mercuric chloride (0.1%HgCl2 W/V) for 5 min and then rinsed with sterile distilled water six times. If the plant seeds were very sensitive to 2%NaCIO, it would be advisable to use 10%H2O2 (v/v) instead of 2% NaCIO.